2019
DOI: 10.1038/s41431-019-0363-z
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation of the role of pathogenic SMAD6 variants in bicuspid aortic valve-related aortopathy

Abstract: Progressive dilatation of the thoracic aorta leads to thoracic aortic aneurysm (TAA), which is often asymptomatic but predisposes to lethal aortic dissections and ruptures. TAA is a common complication in patients with bicuspid aortic valve (BAV). Recently, rare loss-of-function SMAD6 variants were shown to contribute significantly to the genetic aetiology of BAV/TAA. Intriguingly, patients with craniosynostosis have also been reported to be explained molecularly by similar lossof-function SMAD6 variants. Whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 34 publications
(65 reference statements)
1
43
0
3
Order By: Relevance
“…An enrichment of SMAD6 variants considered to be pathogenic has been reported in several pathologies distinct from CRS. [10][11][12][13][14][15][16][17] Using our variant categorization (based on AF and DS), we evaluated all SMAD6 variants that were previously reported as pathogenic. Systematic review identified 74 different SMAD6 variants, including 30 missense (Table S4, Fig.…”
Section: Re-evaluation Of Smad6 Variants Previously Reported As Pathomentioning
confidence: 99%
See 2 more Smart Citations
“…An enrichment of SMAD6 variants considered to be pathogenic has been reported in several pathologies distinct from CRS. [10][11][12][13][14][15][16][17] Using our variant categorization (based on AF and DS), we evaluated all SMAD6 variants that were previously reported as pathogenic. Systematic review identified 74 different SMAD6 variants, including 30 missense (Table S4, Fig.…”
Section: Re-evaluation Of Smad6 Variants Previously Reported As Pathomentioning
confidence: 99%
“…4 SMAD6, originally identified in mammals by homologybased cloning, 5,6 encodes one of two (with SMAD7) inhibitory members of the SMAD family required for regulated intracellular signal transduction by members of the transforming growth factor β/bone morphogenetic protein (TGFβ/BMP) superfamily. [7][8][9] Intriguingly, enrichment of rare SMAD6 variants has also been reported in association with several other distinct phenotypes, namely congenital heart disease, [10][11][12] bicuspid aortic valve (BAV) and ascending thoracic aortic aneurysm (TAA), [13][14][15] intellectual disability, 16 and radioulnar synostosis. 17 In a follow-up study, Timberlake et al increased the sample size of probands with midline CRS and no other genetic diagnosis to 379 (45 pedigrees included ≥1 additional affected family member).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another example is the SMAD6 R12X nonsense mutation present in all three affected members of family TN. Some patients with loss of function mutations in SMAD6 have neurological abnormalities25 while others have not,26 suggesting variable penetrance. Our analysis shows there are no likely pathogenic variants on the hemizygous region of chromosome 16 in TN, suggesting modifying loci are present elsewhere in the genome.…”
Section: Discussionmentioning
confidence: 99%
“…BAV may be asymptomatic and undetected in early life but poses a risk for serious complications and sudden cardiac death later in life 5 . The extreme clinical variability, reduced penetrance, and suspected genetic heterogeneity have complicated the identification of genes involved in non‐syndromic CHD, with only a limited number of genes identified to date 6‐9 …”
Section: Introductionmentioning
confidence: 99%